Analysis and design of a power supply - Muhammad Said Bin Ali (Nanyang Technological University, 2023)
A power supply is a necessary component of any electronic device, its main role is to supply a specific voltage and current to an electrical device without causing it damage. Power supply operates by taking in the input voltage from an AC power source and convert it to a suitable DC voltage. The DC voltage has to be stable and constant in order to avoid damaging the electronic device it is powering. There are two types of power supply linear or switching. Linear power supply is less complex than that of a switching power supply however, it has many disadvantages compared to a switching power supply which is more efficient and lighter. Even though the switching power supply has more advantages compared to the linear power supply, a linear power supply is more commonly used in areas such as hospital and communication devices as it does not generate high amount of noise that will affect the reading of these sensitive equipment. A power supply can be grouped depending on its uses, such as AC to DC or DC to DC power supply. This project aims to analyze, design, and build a working power supply that is able to deliver up to 30V 2A with both voltage and current control. Additionally, the final product will solve the disadvantages it has compared to a switching power supply.